2019
DOI: 10.1016/j.jceh.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Urinary Metabolic Profile of Liver Fluke-Associated Cholangiocarcinoma

Abstract: Background: Human infection with Opisthorchis viverrini, a carcinogenic liver fluke inhabiting the biliary tree, is endemic in Southeast Asia. Chronic infection is associated with a fatal complication, cholangiocarcinoma (CCA), a late-presenting and aggressive malignancy. Currently, annual mortality rates from CCA mirror trends in incidence, due in part to limited availability of efficient prognostic and early diagnostic biomarkers. With ability to detect thousands of urinary metabolites using metabonomics, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…An association of xanthine oxidoreductase expression and oxidative stress, cancer aggressiveness, and poor clinical outcome has been reported (56). A previous study suggested that purine metabolites in the urine of patients with CCA showed increased levels of uric acid and 7-methylguanine, and reduced levels of hypoxanthine compared with a control group (11). In the present study, the higher levels of inosine in the praziquantel-treated group were negatively correlated with inflammation.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…An association of xanthine oxidoreductase expression and oxidative stress, cancer aggressiveness, and poor clinical outcome has been reported (56). A previous study suggested that purine metabolites in the urine of patients with CCA showed increased levels of uric acid and 7-methylguanine, and reduced levels of hypoxanthine compared with a control group (11). In the present study, the higher levels of inosine in the praziquantel-treated group were negatively correlated with inflammation.…”
Section: Discussionsupporting
confidence: 68%
“…It was found that altered bile acid and phosphatidylcholine metabolism might play an important role in the carcinogenesis processes of CCA (9). Moreover, the urinary metabolic profiles in CCA compared with hepatocellular carcinoma, metastatic secondary liver cancer, pancreatic cancer and ovarian cancer revealed that the levels of acylcarnitine, bile acid, and purine were significantly elevated in CCA compared with controls (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the key role they play in intestinal uptake of lipids and vitamins, bile acids act as signaling molecules that regulate cell growth, as well as inflammation [36]. As such, perturbation of bile acid synthesis is known to be a factor in a variety of cancer types, such as colorectal cancer [37], hepatocellular carcinoma [38], and cholangiocarcinoma [39].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic cholestasis and cholangitis may further lead to secondary cirrhosis of the liver and are susceptible to hepatobiliary cancer. In addition, this group also identified that purine metabolism and lipid metabolism have changed in the CCA urine metabolome in Opisthorchis viverrini -induced liver fluke-associated CCA [ 98 ]. Several comprehensive analyses merged with transcriptome, proteome and metabolome profiles of CCA have been published [ 99 , 100 , 101 , 102 , 103 ].…”
Section: Metabolomics Analysis Of Oncometabolites and Metabolic Rementioning
confidence: 99%